Vitamin K–Dependent Protein S: Beyond the Protein C Pathway - Dahlbäck, Björn (Seminars in Thrombosis and Hemostasis, 2018)
Protein S is a vitamin K–dependent plasma glycoprotein circulating in plasma at a concentration of around 350 nM. Approximately 60% of protein S in human plasma is bound to the complement regulatory protein C4b-binding protein (C4BP) in a high-affinity, high-molecular-weight complex. Protein S in plasma has multiple anticoagulant properties and heterozygous protein S deficiency is associated with increased risk of venous thrombosis. Homozygous deficiency in man and mice is associated with severe thrombosis in fetal life, defects in the vascular system development, and not compatible with life. Protein S has additional functions beyond being an anticoagulant. It affects the complement regulatory properties of C4BP, and moreover, protein S interacts with tyrosine kinase receptors of the TAM family, which comprises Tyro3, Axl, and Mer. The TAM receptor interaction is important for the ability of protein S to stimulate phagocytosis of apoptotic cells. This review will discuss the multiple functions of protein S, describing its role as cofactor to activated protein C with a subsequent focus on the other functions of protein S.
Keywords: Gas6; Axl; Tyro3; Mer; C4b-binding protein; C4BP; protein C; blood coagulation